2004
DOI: 10.1099/vir.0.19472-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of intratypic recombination in natural populations of hepatitis C virus

Abstract: Hepatitis C virus (HCV) has high genomic variability and, since its discovery, at least six different types and an increasing number of subtypes have been reported. Genotype 1 is the most prevalent genotype found in South America. In the present study, three different genomic regions (59UTR, core and NS5B) of four HCV strains isolated from Peruvian patients were sequenced in order to investigate the congruence of HCV genotyping for these three genomic regions. Phylogenetic analysis using 59UTR-core sequences f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
2
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 52 publications
(43 reference statements)
3
85
2
2
Order By: Relevance
“…Only one of the intragenotype recombinants described involved genotype 4 [140] , four involved different subtypes of genotype 1 and the remaining four involved different subtypes of genotype 6. Examples of recombinants (1a/1b) have been identified in Peru as well as in Uruguay [111,141] and (1a/1c) in Japan and in India [142,143] . Interestingly, although the recombinants reported in Modified from ref.…”
Section: Recombinationmentioning
confidence: 99%
“…Only one of the intragenotype recombinants described involved genotype 4 [140] , four involved different subtypes of genotype 1 and the remaining four involved different subtypes of genotype 6. Examples of recombinants (1a/1b) have been identified in Peru as well as in Uruguay [111,141] and (1a/1c) in Japan and in India [142,143] . Interestingly, although the recombinants reported in Modified from ref.…”
Section: Recombinationmentioning
confidence: 99%
“…Recombination crossover point was NS5B in the intra-genotype recombination case found in Peru, not in the genome coding the first non-structural protein. [Colina et al, 2004 The genotype of HCV influences on the outcome of interferon treatment [Zein, 2000] and the interferon sensitivity has been attributed to the sequence variability of NS5A and E2. [Gale et al, 1998;Gale et al, 1997;Pavio et al, 2002;Polyak et al, 2001;Taylor et al, 2005;Taylor et al, 1999] The recombination events at NS2 in St Petersburg [Kalinina et al, 2002] Bootstrap values (>70%) are given on blanches as percentages from 1,000…”
Section: Identification Of the Recombination Crossover Pointmentioning
confidence: 99%
“…In fact, the natural inter-and intra-genotypic recombinants of HCV (RF1_2k/1b and RF2_1a/1b) were recently found and the crossover points were clearly indicated in NS2 and NS5B regions, respectively. [Colina et al, 2004;Kalinina et al, 2002] The HCV recombination has been reported only in these cases to date. [Simmonds et al, 2005] Several studies reported that the positive rate for anti-HCV was 2.2% among blood donors (Metro Davao, 1990) [Arguillas et al, 1991], and 4.6% among inmates (Metro Manila) [Katayama et al, 1996] in the Philippines.…”
Section: Introductionmentioning
confidence: 99%
“…An instance of such inter-genotypic recombination was observed between genotype 2k and 1b in St. Petersburg by Kalinina et al [9]. Colina et al [6] reported intra-typic recombination between genotype 1a and 1b. The potential for the emergence of novel genetic variants is high due to the increasing subtype diversity in various sub populations.…”
mentioning
confidence: 93%